BIODIVERSITY OF SOIL ARTHROPODS IN BT-COTTON FIELDS COTTON FIELDS OF WARANGAL, ANDHRA PRADESH, INDIA - P. BRAHMAM,; CH. SRAVANTHY,; P. LAXMAN,; CH. SAMATHA,; CH. SAMMAIAH, (The Bioscan, 2010)
A survey of soil arthropods was undertaken in Bt-cotton (Bacillus thrungienesis) fields of Warangal, A.P., from June 2006 to December 2008. Besides, Araneida(spiders) and Acari(mites) four insect orders Collembola, Orthoptra, Hymenoptera, Coleoptera were collected by pitfall traps.